THE USE OF PICTURESIN YOUNG LEARNERS' JOURNAL WRITING(A CASE-STUDY OF THE 3-4 GRADER STUDENT OF ENGLISH FOR YOUNG LEARNERS COURSE IN BALAI BAHASA UPI) - Indiana Ayu Alwasilah, - (2011)
This study centered around the issues of the use of pictures in young learners' journal writing. It is aimed to discover the teaching implementation of using picture in young learners' journal writing. Moreover, it examines how picture could stimulate the young learners to write, and their responses toward the learning. This study was conducted from the consideration that literacy skills, particularly writing, should be introduced since childhood (Alwasilah, 1999; Nagin, 2006). Analysis of the research literature revealed that writing is considered as the most difficult skill to acquire (Hudelson, 1989; Heaton, 1995; Ioannou-Georgiou & Pavlou, 2003; Brown, 2004; Paul, 2006). Moreover, it was discovered that the use of picture is appropriate to be used as an aid in teaching writing (Broughton, et al 1978; Bates 1991, in Schweizer 1999). Beside that, the journal as a tool to teach writing is properly used since it occupies a remarkable role in a pedagogical model (Brown, 2004). A case-study design was used in this study, and the data were collected through observation, interview, and written documents to gain relevant data. The data from these three instruments were analyzed qualitatively. The results of the study were in line with the previous findings from the studies conducted by Sands (1956), Sinatra (1986), Bates (1991) in Schweizer (1999), and Sagita (2009); that pictures are effective to be used as teaching aids, since the young learners showed great attention during the lesson. The research findings of this study discover some benefits of pictures, as follows: (1) to help students remember vocabulary; (2) to keep the students engaged in the activity; (3) to keep students' attention span longer; (4) to lessen students' writing problems on accuracy, task achievement, handwriting, and mechanics; (5) to stimulate the students to use their dictionary; and (6) to encourage the students to have better writing strategies. In other words, the use of pictures has significant influence on young learners' writing. For that reason, this kind of method is recommended to be used on teaching writing to young learners.